GAMBARAN KINERJA PERAWAT DALAM MENDOKUMENTASIKAN ASUHAN KEPERAWATAN BERBASIS KOMPUTER - Intan Diah Pramithasari (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to identify the application of innovation-based documentation system computer technology.  Methods: Explorative descriptive study using a quantitative approach. The population in this study is all nurses in inpatient hospitals Banyumas. The sampling technique used in this study is simple random sampling in order to obtain a total sample of 76 people. While the nurses performance appraisal obtained through observation of nursing documentation, which were selected based on purposive sampling technique Results: The results of this study showed that based on the minimum standards of service, the performance of nurses in documenting computer-based nursing care in hospitals Banyumas in good category (52.6%). The results of the frequency distribution was found that the majority of nurses in hospitals Banyumas female (69.7%), education diploma (84.2%), with an average age of nurses is in the range optimal working age (57.9%) and had working period in the range of intermediate tenure (63.2%). Conclusion: The implementation of this system is expected to improve the performance of nurses in documenting nursing care.